FARM Household Resilience, Income Source and Earnings (FARM-RISE) - Wilson, Paul; Caskie, Paul (International Journal of Population Data Science, 2025)
Objectives Policy makers lack data on farm household (FHH) incomes, resilience and hardship, both across FHH and relative to non-farm rural households. FARM-RISE will use the Administrative Data | Agricultural Research Collection (AD|ARC) data [2011] informed by other data analysis to provide key insights to policy makers, farm households and researchers. Methods Informed by stakeholder workshops and a steering group, FARM-RISE will estimate farm households’ (FHH) financial resilience and hardship using the (AD|ARC) data. The AD|ARC data contains information about business turnover, household composition and household employment. To estimate farm business profit, or private drawing, coefficients will be estimated from the Farm Business Survey (FBS); to estimate employment earnings, the Annual Survey of Hours and Earnings (ASHE) will be drawn upon to link FHH employment to off-farm FHH earnings. Using Probit, Multivariate and Difference-in-Difference approaches, key drivers of FHH income will be estimated and compared to those from non-farm rural households. Results To date, activity has focused on reviewing the state-of-the-art literature, achieving steering group direction on important topics of consideration, and holding stakeholder workshop activities. Analysis of FBS data has demonstrated that the proportion of farm revenue retained as private drawings over 2009-2012 averaged approx. 17.5% across England and Wales. While this proportion varied by farm type and location, farm size was the greatest driver of proportion retained as private drawings. Future analysis will explore ASHE data to provide coefficients to estimate earning from AD|ARC data. Subsequent analysis will be based on an augmented AD|ARC dataset, informed by the coefficients generated from FBS and ASHE analysis. Initial results are anticipated late summer 2025, ahead of the ADR conference. Conclusion Utilising ADR data from AD|ARC collection, when appropriately informed by stakeholder engagement and external data set analysis offers potential for new insights to be generated that will inform future research opportunities and agricultural and social security policies. Future research will explore in greater depth ADR opportunities for public benefit.